\(\frac{3x-y}{x+y}\)\(=\)...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1 tháng 12 2020

\(\frac{3x-7}{x+y}=\frac{3}{4}\)

\(\Rightarrow4\left(3x-y\right)=3\left(x+y\right)\)

\(12x-4y=3x+3y\)

\(9x=7y\)

\(\frac{x}{y}=\frac{7}{9}\)

1 tháng 12 2020

\(\frac{3x-y}{x+y}=\frac{3}{4}\Leftrightarrow4\left(3x-y\right)=3\left(x+y\right)\)

\(\Leftrightarrow12x-4y=3x+3y\Leftrightarrow9x-7y=0\)

\(\Leftrightarrow9x=7y\Leftrightarrow\frac{x}{y}=\frac{7}{9}\)

Vậy \(\frac{x}{y}=\frac{7}{9}\)

1 tháng 12 2019

1. Ta có:

\(\frac{1}{x}+\frac{1}{x\left(x+1\right)}+\frac{1}{\left(x+1\right)\left(x+2\right)}+...+\frac{1}{\left(x+2013\right)\left(x+2014\right)}\)

\(=\frac{1}{x}+\frac{1}{x}-\frac{1}{x+1}+\frac{1}{x+1}-\frac{1}{x+2}+...+\frac{1}{x+2013}-\frac{1}{x+2014}\)

\(=\frac{2}{x}-\frac{1}{x+2014}\)

\(=\frac{2\left(x+2014\right)}{x\left(x+2014\right)}-\frac{x}{x\left(x+2014\right)}\)

\(=\frac{2x+4028-x}{x\left(x+2014\right)}=\frac{x+4028}{x\left(x+2014\right)}\)

1 tháng 12 2019

2a) ĐKXĐ: x \(\ne\)1 và x \(\ne\)-1

b) Ta có: A = \(\frac{x^2-2x+1}{x-1}+\frac{x^2+2x+1}{x+1}-3\)

A = \(\frac{\left(x-1\right)^2}{x-1}+\frac{\left(x+1\right)^2}{x+1}-3\)

A = \(x-1+x+1-3\)

A = \(2x-3\)

c) Với x = 3 => A = 2.3 - 3 = 3

c) Ta có: A = -2

=> 2x - 3 = -2

=> 2x = -2 + 3 = 1

=> x= 1/2

2 tháng 3 2020
https://i.imgur.com/qz7eYvL.jpg
2 tháng 3 2020

a.\(\frac{1-3x}{2}-\frac{x+3}{2}=\frac{1-3x-x-3}{2}=\frac{1-4x-3}{2}=\frac{-4x-2}{2}=\frac{-2\left(2x+1\right)}{2}=-2x-1\)

b. \(\frac{2\left(x+y\right)\left(x-y\right)}{x}-\frac{-2y^2}{x}=\frac{2\left(x^2-y^2\right)+2y^2}{x}=\frac{2x^2-2y^2+2y^2}{x}=2x\)

c. \(\frac{3x+1}{x+y}-\frac{2x-3}{x+y}=\frac{3x+1-2x+3}{x+y}=\frac{x+4}{x+y}\)

d. \(\frac{xy}{2x-y}-\frac{x^2-1}{y-2x}=\frac{xy}{2x-y}-\frac{1-x^2}{2x-y}=\frac{xy-1+x^2}{2x-y}\)

e. \(\frac{4x-1}{3x^2y}-\frac{7x-1}{3x^2y}=\frac{4x-1-7x+1}{3x^2y}=\frac{-3x}{3x^2y}=\frac{-1}{xy}\)

30 tháng 12 2018

Từ \(\frac{x}{y-z}+\frac{y}{z-x}+\frac{z}{x-y}=0\Rightarrow\frac{x}{y-z}=-\frac{y}{z-x}-\frac{z}{x-y}\)

\(\Rightarrow\frac{x}{y-z}=\frac{y}{x-z}+\frac{z}{y-x}\)

\(\Leftrightarrow\frac{x}{y-z}=\frac{y\left(y-x\right)+z\left(x-z\right)}{\left(x-z\right)\left(y-x\right)}\)

\(\Leftrightarrow\frac{x}{y-z}=\frac{y^2-xy+zx-z^2}{\left(x-z\right)\left(y-x\right)}\)

\(\Leftrightarrow\frac{x}{\left(y-z\right)^2}=\frac{y^2-xy+zx-z^2}{\left(x-z\right)\left(y-x\right)\left(y-z\right)}\)

C/m tương tự đc \(\frac{y}{\left(z-x\right)^2}=\frac{z^2-yz+xy-x^2}{\left(x-z\right)\left(y-z\right)\left(y-z\right)}\)

                          \(\frac{z}{\left(x-y\right)^2}=\frac{x^2-xz+zy-y^2}{\left(x-z\right)\left(y-x\right)\left(y-z\right)}\)

Khi  đó \(Q=\frac{y^2-xy+xz-z^2+z^2-yz+xy-x^2+x^2-xz+yz-y^2}{\left(x-z\right)\left(y-x\right)\left(y-z\right)}=0\)

Vậy Q=0

14 tháng 12 2016

\(\frac{x+y}{z}+\frac{y+z}{x}+\frac{z+x}{y}=\frac{x+y+z}{z}-1+\frac{x+y+z}{y}-1+\frac{x+y+z}{x}-1\)

\(=\left(x+y+z\right)\left(\frac{1}{x}+\frac{1}{y}+\frac{1}{z}\right)-3=0-3=-3\)